Effect of fungicides and bioagents against Colletotrtcnum capsici on seed quality of Chilli - and H.S. SHETTY, C. SRINIVAS, S.R. NIRANJANA*, L. PRAVEEN KUMAR, S. CHANDRA NAYAKA (Indian Phytopathology, 2006)
Five different cultivars of chilli seeds infected to a varied degree by Colletotrichum capsici were treated with biocontrol agents and fungicides. Pure cultures of Pseudomonas fluorescens and Trichoderma harzianum at the rate of 1 x 108 cfu g.l and their talcum based formulations (28 x 107 cfu g.l and 19 x 107 cfu g.l) at the rate of 5g kg1 and 10g kg1 of seeds were used, respectively. The treated seeds were evaluated for percent reduction of Colletotrichum capsici, seed germination, vigour index and field emergence. It was found that pure culture of P. fluorescens was more effective in reducing C. capsici infection followed by T. harzianum than the fungicides treated and untreated seeds. Formulations of P. fluorescens were also effective in reducing C. capsici infection and in increasing the seed germination, vigour index and field emergence, followed by T. harzianum and fungicide treatments in comparison with control.